Non-Financial Reporting of Insurance Companies: Case of Croatia - Mirjana HLADIKA; Ana PULJIZ (Communications of International Proceedings, 2022)
Over the past few decades increasing number of companies, in addition to financial statements, started to report on information related to environmental, social and personnel issues as well as issues related to human rights and the battle against corruption and bribery. Considering insurance companies are significant institutional investors of the financial market in every country, in this paper an analysis of GRI compliance was conducted and comparison of non-financial statements was made for twelve insurance companies operating in the Croatian market. A sample was divided into two groups, insurance companies which are obliged to report non-financial information and insurance companies that report them voluntarily. The main goal of the analysis in this paper is to assess the state of non-financial reporting of insurance companies in the Republic of Croatia over the period from 2017 to 2019 and to investigate the level and type of disclosed non-financial information in insurance companies that are obliged to present non-financial reports and insurance companies that present non-financial reports voluntary. This analysis is important for the investors and other stakeholders for the purpose of making business decisions especially investment decisions. According to the results, it can be concluded that the non-financial reports of insurance companies are generally characterized by a high level GRI compliance in all three categories. There is no significant difference in compliance in all three categories for both groups of sample. It was found that insurance companies that are not obliged to report non-financial information have a higher level of GRI compliance in economic and social category whereas insurance companies that are obliged to report non-financial information have a higher level of GRI compliance in environmental category.
Keywords: non-financial reporting; non-financial information; GRI compliance; insurance companies; Croatia